Happy Living in Darkness! Indoor Lighting in Relation to Activities of Daily Living, Visual and General Health in 75-Year-Olds Living at Home. Issue 2 (2nd April 2016) - Eilertsen, Grethe; Horgen, Gunnar; Kvikstad, Tor Martin; Falkenberg, Helle K.
ABSTRACT: Lighting has been identified as a significant environmental attribute for promoting vision and general health among older people, enabling successful aging at home, but it has received little attention in the literature. Indoor lighting levels, self-reported vision and general health, and activities of daily life were measured in 114 healthy 75-year-old Norwegians. Despite very low levels of indoor lighting, the subjects were happy and healthy. There is a large discrepancy between self-assessed health and recommended lighting levels, and low awareness of the effect of lighting on age-related vision loss or daily living in the future. Knowledge of how to utilize indoor lighting to ensure healthy and safe aging in the home is needed.